2016
DOI: 10.1016/j.ydbio.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Novel action of FOXL2 as mediator of Col1a2 gene autoregulation

Abstract: FOXL2 belongs to the evolutionarily conserved forkhead box (FOX) superfamily and is a master transcription factor in a spectrum of developmental pathways, including ovarian and eyelid development and bone, cartilage and uterine maturation. To analyse its action, we searched for proteins that interact with FOXL2. We found that FOXL2 interacts with specific C-terminal propeptides of several fibrillary collagens. Because these propeptides can participate in feedback regulation of collagen biosynthesis, we inferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…The genetic interaction between the oim allele and homotrimeric collagen (I) could relate to the process of collagen folding and trimerization within the endoplasmic reticulum, or indeed the homotrimeric collagen (I) could alter cellmatrix interactions to modulate cellular stress responses. Procollagen N and Cpropeptides, derived from the proteolytic cleavage of procollagen, have been shown to have intracellular roles in modulating protein synthesis (Hayata et al, 2008;Marongiu et al, 2016;Oganesian et al, 2006) whilst homotrimeric triple helical regions increased proliferation and migration as compared to heterotrimeric pepsinised collagen (Makareeva et al, 2010). Hence homotrimeric forms of collagen fibrils or propeptides have the potential for altered signalling affecting cellular stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic interaction between the oim allele and homotrimeric collagen (I) could relate to the process of collagen folding and trimerization within the endoplasmic reticulum, or indeed the homotrimeric collagen (I) could alter cellmatrix interactions to modulate cellular stress responses. Procollagen N and Cpropeptides, derived from the proteolytic cleavage of procollagen, have been shown to have intracellular roles in modulating protein synthesis (Hayata et al, 2008;Marongiu et al, 2016;Oganesian et al, 2006) whilst homotrimeric triple helical regions increased proliferation and migration as compared to heterotrimeric pepsinised collagen (Makareeva et al, 2010). Hence homotrimeric forms of collagen fibrils or propeptides have the potential for altered signalling affecting cellular stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively the homotrimeric collagen (I) could alter cell-matrix interactions to modulate cellular stress responses, if present. Procollagen N-and Cpropeptides, derived from the proteolytic cleavage of procollagen, have been shown to have intracellular roles in modulating protein synthesis (56)(57)(58) whilst homotrimeric triple helical regions increased proliferation and migration as compared to heterotrimeric pepsinised collagen (11). Hence homotrimeric forms of collagen fibrils or propeptides have the potential for altered signalling affecting cellular stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that ERG-targeted genes, like IGF2 and IGFBP1 [21] were upregulated, while some interactive genes, such as homeobox genes, Hoxc6, 8, 9, 5, and Hoxb7, 6, 3, as well as Hoxa9, 7 [22][23][24] were downregulated in horn bud tissues of polled goats (Additional file 3: Table S1). In addition, FOXL2-regulated genes, such as some collagen genes [25] , were upregulated in the horn bud tissues of polled goats too (Additional file 3: Table S1). pairwise comparison between horn bud and skin of polled and horned goats, as well as between horn bud of horned and polled goats.…”
Section: Gene Expression Studies Reveal Novel Horn Development-specific Candidatesmentioning
confidence: 99%
“…Potential FOXL2 targets revealed by ChIP and RT-PCR implicated its involvement in follicular and craniofacial development [ 18 20 ]. It has been also shown that FOXL2 affects collagen synthesis [ 21 , 22 ]. Nicol et al .…”
Section: Introductionmentioning
confidence: 99%